Pengaruh Kedisiplinan Dan Komunikasi Kerja Terhadap Kinerja Karyawan - Ella Anastasya Sinambela; Yusuf Rahman Al Hakim; Moch. Irfan (RELASI : JURNAL EKONOMI, 2019)
Every company should try to develop the quality of human resources as the basic foundation for running the company's processes. In fact, only companies that pay attention to the quality of human resources can continue to survive business competition. The quality of human resources in the company is monitored through its behavior and job performance. One way to control employee behavior is through disciplinary programs. Besides that, it is also necessary to create a conducive working environment through good working communication among members of the organization. This study aims to analyze and discuss the effects of discipline and communication on job performance. The sampling technique uses non-probability sampling method with total sampling technique. The population in this study is the community, with a total sample of 93 respondents. The analysis tool used is multiple linear regression with the help of SPSS 24.0 for Windows software. The results of the study show that discipline and communication have a significant positive effect on job performance.